Higher-Order Thinking Abilities for Improved Critical Thinking in Thermochemical Materials Module - Aida Auliyani; Abdul Gani*; Adlim Adlim (Jurnal Pendidikan Kimia Indonesia, 2022)
The use of teaching materials that support higher-order thinking skills (HOTS) on thermochemical materials still needs to be improved, which makes students' critical thinking skills (CBC) low. The goal of this study is to find out if HOTS-based chemistry learning modules on thermochemical materials and improving CBC are possible and what students think of them when they are used. This study is a type of development research called "ADDIE" research. Three experts on materials, three experts on the media, and three teachers took part in this study. As the control group, 35 people were used, and as the experimental group, 36 people were used. In this study, both non-test and test methods were used to collect data. The non-test method was done with the help of a product validity questionnaire sheet, which was a research tool. On the other hand, the instrument test looked at how well students could think critically. Descriptive qualitative analysis, quantitative statistics, and inferential statistics are used to look at the data (t-test). The average CBC of students was different before and after they used HOTS-based chemistry modules to study thermochemistry materials. The results show that using HOTS-based chemistry modules to improve students' CBC is better than using standard modules. It was decided that chemistry modules based on HOTS could help students learn how to think more critically.